Theologian Nurgali Khasanov: Resilience throughout life - R.I. Malikov (Ученые записки Казанского университета: Серия Гуманитарные науки, 2020)
The fate of Nurgali Khasanov, the distinguished Muslim theologian of the Middle Volga region, sheikh, and akhund, was discussed. His life path, full of not only bright events, tireless work, recognition and fame, but also of ordeals and grief, was reconstructed on the basis of the work “Grateful Feelings of Bright Journeys” dedicated to pilgrimage, his autobiographical collection “58 Years of Travel in One Century”, as well as using the materials from the foundation of the Simbirsk provincial government, the Simbirsk provincial gendarmerie department, the State Archive of the Ulyanovsk Region, the Tatar newspapers (“Koyash”, “Yoldyz”, “Azad”, “Өlfәt”), and the “Mәglүmat” magazine. The events described cover the period of life of the theologian from 1852 up to 1919. The study is highly relevant, because the personality of Nurgali Khasanov has been insufficiently investigated in Russian historiography. The strengths of his character, tolerance for ordeals, and wisdom were shown. With the help of the biographical description of his outstanding personality, it seems possible to perceive the historical processes of that time, to understand the difficulties encountered by Muslim religious figures and theologians of the Middle Volga region during the late 19th–early 20th centuries.